Management Strategy of Village-Owned Enterprises (BUMDes) in Local Economic Development: A Study of BUMDes Binangun Sendang Artha, Kulon Progo - Yulianto Yulianto; Luhfi Wibawa; Yudan Hermawan; Kiki Irafa Candra; Sofia Nuria Lisa (MALLOMO: Journal of Community Service, 2026)
This study examines the management strategy of BUMDes Binangun Sendang Artha in supporting local economic development in Sendangsari Village, Pengasih District, Kulon Progo Regency, Indonesia. The research employed a qualitative approach using a single case study design to explore institutional governance, community participation, business development, and supporting and inhibiting factors in BUMDes management. Data were collected through in-depth interviews, observation, and documentation involving BUMDes administrators, village government officials, and community members. The findings show that BUMDes plays an important role in strengthening the local economy through microfinance services, particularly savings and loan activities that support microenterprises and productive community businesses. The success of BUMDes is influenced by strong social trust, active community participation, and support from the village government. However, several challenges remain, including limited human resource capacity, low business innovation, limited diversification of business units, and weak digital literacy. The study identifies institutional strengthening, business innovation, and cross-sector partnerships as key strategies for improving BUMDes sustainability and competitiveness. This research highlights the importance of community-based economic institutions in promoting inclusive and sustainable rural development.